Application of solid-phase microextraction to in vitro skin permeation experiments: example using diethyl phthalate - Frasch, H. Fred; Barbero, Ana M. (Toxicology in vitro, 2005)
The application of automated solid-phase microextraction (SPME) as a sample preparation technique for in vitro studies of skin permeation is described, using diethyl phthalate (DEP) as an example. In vitro diffusion cell experiments and skin–vehicle partition coefficient determinations require quantitative analysis of low-level analytes in aqueous samples. SPME is an ideal candidate for sample preparation for subsequent gas chromatographic analysis, offering numerous advantages over other methods. SPME conditions were optimized and the automated method was found to exhibit adequate sensitivity and good precision (relative standard deviation = 3%). Abdominal skin (dermatomed at 350 μm) from male hairless guinea pigs ( n = 6) was used to measure DEP skin permeation parameters. In vitro methods were employed to determine permeability coefficient ( k p), time lag ( τ) and skin–buffer partition coefficient ( K SB) for 2 mM DEP in HEPES buffered Hanks Balanced Salt Solution. Measurements (mean ± standard deviations) are: k p, 0.021 ± 0.012 cm/h; τ, 0.67 ± 0.18 h; K SB, 4.74 ± 0.68. The skin may be a significant route for the uptake of DEP.